Clinicopathological case: progressive somnolence and dementia in an accountant: when the shine rubs off the gold standard. Issue 6 (4th August 2018) - Soane, Tim; Schott, Jonathan M; Stone, Jon; Smith, Colin; Pal, Suvankar; Davenport, Richard J
Abstract : A 63-year-old accountant developed progressive somnolence, cognitive decline, gait disturbance and cerebellar dysfunction with autonomic features. This report documents the clinicopathological conference at the 39th Edinburgh Advanced Neurology Course 2017.